Thermoneutrality and Immunity: How Does Cold Stress Affect Disease? - Vialard, Fiorella; Olivier, Martin (Frontiers in Immunology, 2020)
One of the major challenges the scientific community faces today is the lack of translational data generated from mouse trials for human health application. Housing temperature-dependent chronic cold stress in laboratory rodents is one of the key factors contributing to lack of translatability because it reveals major metabolic differences between humans and rodents. While humans tend to operate at temperatures within their thermoneutral zone, most laboratory rodents are housed at temperatures below this zone and have an increased energy demand to generate heat. This has an impact on the immune system of mice and thus affects results obtained using murine models of human diseases. A limited number of studies and reviews have shown that results obtained on mice housed at thermoneutrality were different from those obtained from mice housed in traditional housing conditions. Most of those studies, focused on obesity and cancer, found that housing mice at thermoneutrality changed the outcomes of the diseases negatively and positively, respectively. In this review, we describe how thermoneutrality impacts the immune system of rodents generally and in the context of different disease models. We show that thermoneutrality exacerbates cardiovascular and auto-immune diseases; alleviates asthma and Alzheimer’s disease; and, changes gut microbiome populations. We also show that thermoneutrality can have exacerbating or alleviating effects on the outcome of infectious diseases. Thus, we propose that in order to refine murine models of disease and increase their translational capacity, housing at thermoneutrality must be considered for any trial involving rodents.